2010
DOI: 10.1016/j.envpol.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-element accumulation near Rumex crispus roots under wetland and dryland conditions

Abstract: Rumex crispus was grown under wet and dry conditions in two-chamber columns such that the roots were confined to one chamber by a 21 μm nylon mesh, thus creating a soil–root interface (‘rhizoplane’). Element concentrations at 3 mm intervals below the ‘rhizoplane’ were measured. The hypothesis was that metals accumulate near plant roots more under wetland than dryland conditions. Patterns in element distribution were different between the treatments. Under dryland conditions Al, Ba, Cu, Cr, Fe, K, La, Mg, Na, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…J-172 and Salix babylonica L. (Chen et al 2012). Kissoon et al (2010) also found the flooding significantly increased metal (Cu, Fe, and Mn) uptake by Rumex Crispus L. It was suggested that iron plaque formed on root surface in flooding conditions reduced the uptake of metals by plants because of its iron hydroxide functional groups (Batty et al 2000;Liu et al 2011a). The increase in HMs in the roots was partly due to the retention effect of HMs by iron plaques on the root surface.…”
Section: Effect Of Bbc and Flooding On Phytoremediation Capacity Of S...mentioning
confidence: 92%
“…J-172 and Salix babylonica L. (Chen et al 2012). Kissoon et al (2010) also found the flooding significantly increased metal (Cu, Fe, and Mn) uptake by Rumex Crispus L. It was suggested that iron plaque formed on root surface in flooding conditions reduced the uptake of metals by plants because of its iron hydroxide functional groups (Batty et al 2000;Liu et al 2011a). The increase in HMs in the roots was partly due to the retention effect of HMs by iron plaques on the root surface.…”
Section: Effect Of Bbc and Flooding On Phytoremediation Capacity Of S...mentioning
confidence: 92%
“…This has predefined the choice of methods to atomic absorption spectrometry (AAS) and ICP-AES and ICP-MS. Recently, however, many less studied elements such as REEs and platinum metals are increasingly used in different technological processes and present potential ecological problems on the one hand, though, on the other hand, some of them may be beneficial to plant growth (39,40) or correlate with other elements in the plant (1, 2). Thus, the necessity to determine as many elements as possible in different concentration intervals demands the use of methods and/or a combination of methods permitting multielement analysis with high accuracy and precision.…”
Section: Instrumental Measurementmentioning
confidence: 99%
“…For instance, metal sorption on the organic matter accumulated in the rhizosphere and on the Fe/Mn root plaque contributes to higher metal accumulation in the macrophyte rhizosphere (McCabe et al, 2001;Otte et al, 2004). However, through root exudation and acidification, metals can be mobilized for uptake (Kissoon et al, 2010). Consequently, wetland plants are frequently more exposed to higher metal concentrations than dryland plants: e.g.…”
Section: Intra-specific Variability Of Root Biomass Production Acrossmentioning
confidence: 99%
“…Consequently, wetland plants are frequently more exposed to higher metal concentrations than dryland plants: e.g. metal uptake in Rumex crispus L. was 2.5 times higher under wetland compared to dryland conditions (Kissoon et al, 2010).…”
Section: Intra-specific Variability Of Root Biomass Production Acrossmentioning
confidence: 99%
See 1 more Smart Citation